Assessment of the risk factors for low birth weight at Kitenge Hospital, Mbujimayi City, Democratic Republic of the Congo: 2018 - 2022 - Kitengie, Bâtisseure Luyenga; Ngiele, Constantine Malobo; Salamayi, Yannick Salamayi; Kitunga, Charlotte Kitenge; Lutumba, Pascal; Kafinga, Emery Luzolo; Mawunu, Monizi; Mudogo, Virima; Ngbolua, Koto-Te-Nyiwa; Mukandu, Basua Babintu Layka (Orapuh Journal, 2024)
Introduction Low birth weight (LBW) is defined as a birth weight of less than 2500 grams (5.5 pounds) and is associated with various health risks. Factors contributing to LBW include premature birth (before 37 weeks gestation), poor maternal nutrition, maternal health issues such as hypertension or infections, teenage pregnancy, multiple pregnancies, substance abuse during pregnancy, lack of prenatal care, and socioeconomic factors such as poverty and limited access to healthcare. Purpose This study was aimed at assessing the risk factors of low birth weight at Kitenge Hospital Mbujimayi City, Democratic Republic of the Congo. Methods The study is a retrospective cross-sectional study conducted on the different risk factors for low birth weight in the gynaecology-obstetrics departments of the Kitenge Hospital in Mbuji-Mayi among women who gave birth and newborns who were well-registered from 1 January 2018 to 31 December 2022. Results The incidence of LBW was 9.13%. LBW affects more newborns born to young mothers (≤19 years) at 41.73%, primiparous at 36.69%, and non-alcoholic at 73.38%. The sex ratio of newborns was 1.72 in favour of girls, and their birth weight was between 1,000 and 2,000 grams (58.99%). Most newborns (50.36%) had attended PNC<4 sessions and 13.67% had not attended PNC (Prenatal consultation) at all. Prematurity dominated the series at 66.19%, and the mother’s young age (≤19 years: OR=3.48), primiparity (OR: 1.48), multiparity (OR: 2.30), alcohol during pregnancy (OR: 2.26) and pregnancy toxaemia (OR: 11.14) were the risk factors statistically associated with LBW in our study setting. Conclusion Low birth weight is a major health problem in our environment. It is highly prevalent, with fatal complications. Low birth weight babies are mainly born to young mothers without proper antenatal care. The integration of the results found into maternal and child health is an important pillar for the well-being of hypotrophic newborns.